Interactions between the gut microbiome and DNA methylation patterns in blood and visceral adipose tissue in subjects with different metabolic characteristics - José Ignacio Martínez-Montoro; Gracia M. Martín-Núñez; Andrés González-Jiménez; Lourdes Garrido-Sánchez; Isabel Moreno-Indias; Francisco J. Tinahones (Journal of Translational Medicine)
Abstract Background The gut microbiome has been reported to induce epigenetic modifications in the host, which may be involved in the pathophysiology of metabolic diseases. Objective To evaluate the potential interactions between the gut microbiome and DNA methylome in subjects with different metabolic characteristics. Methods Sixty-four participants with different metabolic characteristics (i.e., participants without obesity -healthy controls-, and participants with obesity and normal insulin sensitivity/insulin resistance/ type 2 diabetes-T2DM-) were included in this study. A machine learning approach was performed in order to identify distinctive patterns in three omics (gut microbiome, blood DNA methylome, and visceral adipose tissue-VAT- DNA methylome) according to the different study groups. Results Robust distinctive distribution patterns of the three different omics were found between healthy controls and patients with obesity; participants with and without T2DM, and patients with obesity with and without insulin resistance. Importantly, strong correlations between the gut microbiome (including Odoribacteriaceae and Christensenllaceae families) and both blood and VAT DNA methylome were found. Moreover, in the entire study population, three main bacterial genera (Sutterella, Collinsella and Eubacterium) were related to the epigenetic regulation of different genes involved in distinct processes related to cellular metabolism and metabolic diseases, including small ubiquitin-related modifier (SUMO) transferase activity or lipid binding. Conclusion We show that distinctive interactions between the gut microbiome and DNA methylome may occur in subjects with different metabolic characteristics. Further research is needed to elucidate the potential role of these interactions in the pathophysiology of obesity and related comorbidities.